2020
DOI: 10.34172/jlms.2020.67
|View full text |Cite
|
Sign up to set email alerts
|

The Long-term Effects of Percutaneous Laser Disc Decompression (PLDD) Treatment on Lumbar Disc Protrusion: A 2-Year Follow-up

Abstract: Introduction: Nowadays many physicians have focused their attention on using low invasive methods for the treatment of disc protrusion. Thus, the current study was carried out to evaluate the effect and therapeutic outcomes of clinical percutaneous laser disc decompression (PLDD) in the treatment of chronic low back pain caused by disc protrusion during a two-year follow-up. Methods: This historical cohort study was conducted on 40 patients, who were suffering from chronic low back pain caused by disc protrusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In the study conducted by Hashemi et al, there was also a significant reduction in pain intensity and degree of disability in patients who underwent PLDD in the treatment of lumbar pain caused by intervertebral disc protrusion 20 .…”
Section: Discussionmentioning
confidence: 91%
“…In the study conducted by Hashemi et al, there was also a significant reduction in pain intensity and degree of disability in patients who underwent PLDD in the treatment of lumbar pain caused by intervertebral disc protrusion 20 .…”
Section: Discussionmentioning
confidence: 91%
“…This only highlights the need for further research into the potential of QMR techniques as a therapeutic option for the treatment of LR. However, studies on different minimally invasive techniques with a significant follow-up time (over 1 year), which could rationally be expected to include the patient returning to ordinary daily and professional activities, have shown that these types of interventions appear to be safe and effective options for percutaneous lumbar disc decompression [ 37 , 38 , 39 , 40 ], but once again, no definitive conclusions can be established at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Українські автори і ми схильні вважати цю операцію пункційною лазерною мікродискектомією (ПЛМ). Ефективність цієї методики в разі дотримання всіх вимог може сягати 92 % [11][12][13]. Проте пацієнтів, які повністю відповідають вимогам до проведення ПЛМ, не так багато.…”
Section: вступunclassified